Item development for patient-centered care preferences using a three-archetype heuristic: An exploratory study - Logan T. Murry; Julie Urmie; Anthony Olson (Elsevier, 2023)
Background: Patient-centered care is at the center of the Pharmacists' Patient Care Process; however, little is known about patient-centered care preferences and expectations for pharmacist care. Objective: To develop and test items exploring the applicability of a proposed three-archetype heuristic for patient-centered care preferences and expectations in pharmacist care in a population of older adults using community pharmacies that provided enhanced and integrated services. Methods: This was an exploratory analysis of a cross-sectional survey developed and distributed by postal mail to 17 Medicare-eligible patients at five Community Pharmacy Enhanced Service Network (CPESN) pharmacies in Iowa between November 2021 and January 2022. A total of 15 Likert-type archetype survey items were developed with an item developed for each of five constructs (Nature of Relationship and Locus of Control, Care Customization, Care Longevity, Intent of Communication, and Source of Value) for three archetypes ("Partner," "Client," and "Customer").Items were grouped by archetype to yield three, five-item scales, intended to reflect each archetype. Cronbach alphas (α) were calculated for each scale, measuring internal consistency. K-means clustering with silhouette analysis was performed using a group of archetype items with high internal consistency to identify clusters. Kruskal Wallis and Fisher's exact tests used to determine statistical significance for response means and frequencies between clusters, when appropriate. Results: In total, 17 participants completed the survey (100% response rate). Cronbach alphas for the five-item scales reflecting "Partner," "Client," and "Customer" archetypes were 0.66, 0.33, and − 0.03, respectively. K-means clustering identified two clusters, labeled: "Independent Partner" and "Collaborative Partner." There were significant (p-value <0.05) differences between clusters for four of the 15 Likert-type items, suggesting the "Independent Partner" more autonomous, seek pharmacist expertise less frequently, and value pharmacist collaboration less compared to the "Collaborative Partner." Conclusions: The items comprising the "Partner" archetype scale had a reasonably strong level of internal consistency. Older adults may desire highly tailored, co-created experience created from long-standing relationships with a particular pharmacist.